Europe without frontiers: economic, political, civilizational and cultural integration - Krysovatyi, Andrii Ihorovych; Saveliev, Yevhen; Zvarych, Iryna; Koziuk, Viktor; Lyzun, Mariia; Lishchynskyi, Ihor; Kyrylenko, Olha; Kyrylenko, Serhii; Kuryliak, Vitalina; Kuryliak, Maksym; Smaliuk, Halyna; Sokhatska, Olena; et al. (Herald of Economics, 2019)
An analytical note on the results of the International Scientific Conference"Europe without frontiers: economic, political, civilizational and cultural integration", Majorca (Spain), September 14-21, 2018